(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2026)
This article analyzes the theoretical and practical foundations for developing an inversion voltammetric method to determine Pb²⁺ ions in wastewater. The relevance of the topic is обусловлена? Need avoid Russian. Rewrite. The relevance of the topic is determined by the high toxicity of lead, its persistence in aquatic environments, and its ability to pose biological hazards even at low concentrations. The text examines, as an integrated system, the physicochemical essence of inversion voltammetry, its preconcentration stage and anodic recording process, as well as such factors as electrode material, supporting electrolyte, potential regime, time parameters, and matrix effects. Based on the work of Uzbek scientists, bismuth-modified carbon electrodes and biosorption-based preconcentration approaches are substantiated as among the most suitable directions specifically for Pb²⁺ monitoring. Local studies have shown a working range of 10–160 µg/dm³ and R² ≥ 0.98 for the determination of Pb²⁺ and Cd²⁺ on Bi-modified electrodes, while some industrial laboratories have achieved detection down to 10 µg/L with a relative error of about 5%. On this basis, a methodological solution is proposed that relies on sample preparation for wastewater, electrode selection, optimization of the working medium, calibration by the standard addition method, and verification of results under complex matrix conditions.